Comparison of conventional and single bottle system for blood cultures. Issue 6 (June 1988) - Wilson, J A; Barratt, A J; Gray, J; Statham, G B
Abstract : A single bottle blood culture system (Oxoid Signal system) was compared with a conventional two bottle subculturing system. A total of 2016 routine blood samples yielded 186 (9%) clinically important isolates. Of these, 40 (21%) were isolated only in the Oxoid system and 30 (17%) only in the conventional system. One hundred and sixteen (62%) were isolated from both systems. Volume of blood was not significantly associated with the rate of detection but was significantly associated with the speed of detection. A continuation of the study with a Signal bottle and single conventional bottle confirmed initial results of the increased isolation rate using two systems. The Oxoid single bottle blood culture system was at least comparable with a conventional system in terms of rate of detection of organisms and was superior in terms of speed of detection.